Child-Friendly School Management - Hilva Ramadhani; Nabila Amanina (Journal La Edusci, 2026)
This study examines the implementation of Child-Friendly School (CFS) management at Madrasah Ibtidaiyyah Uways Alqorni Pekanbaru as an effort to fulfill and protect children’s rights within the educational environment. Employing a qualitative descriptive approach, data were collected through literature review and field observations to capture school policies, leadership practices, learning processes, and daily interactions that reflect child-friendly principles. The findings reveal that the principal plays a pivotal role in leading and sustaining child-friendly management through rights-based policies, positive discipline, inclusive learning strategies, and collaborative school culture. The implementation of CFS at MI Uways Alqorni emphasizes non-discrimination, student participation, safety, and emotional well-being, contributing to the prevention of violence and bullying while promoting students’ holistic development. Supportive facilities, clear operational procedures, and strong involvement of parents and the community further strengthen the effectiveness of child-friendly practices. The study concludes that effective school leadership and integrated management are key determinants in translating child-friendly policies into sustainable educational practices. These findings highlight the potential of Child-Friendly School management as a practical strategy for improving educational quality and safeguarding children’s rights.